Electrospun drug loaded membranes for sublingual administration of sumatriptan and naproxen - Vrbata, Petr; Berka, Pavel; Stránská, Denisa; Doležal, Pavel; Musilová, Marie; Čižinská, Lucie (International journal of pharmaceutics, 2013)
Sublingual administration of active pharmaceutical substances is in principle favourable for rapid onset of drug action, ready accessibility and avoidance of first pass metabolism. This administration could prove very useful in the treatment of migraines, thus two frequently used drugs were selected for our study. Sumatriptan succinate, naproxen, and its salt as well as combinations of these were incorporated into nanofibrous membranes via the electrospinning process. DSC measurements proved that the resulted membranes contained non-crystalline drug forms. SEM imaging approved good homogeneity of diameter and shape of the membrane nanofibres. The nanofibrous membranes always showed the rapid and mutually independent release of the tested drugs. The drugs exhibited very high differences in sublingual permeation rates in vitro, but the rates of both substances were increased several times using nanofibrous membranes as the drug carrier in comparison to drug solutions. The released drugs subsequently permeated through sublingual mucosa preferentially as non-ionized moieties. The prepared nanofibrous membranes proved very flexible and mechanically resistant. With their drug load capacity of up to 40% of membrane mass, they could be very advantageous for the formulation of sublingual drug delivery systems.
Keywords: Animals; sumatriptan succinate; antiflogistika nesteroidní; aplikace sublinguální; nanovlákna; Migraine; In Vitro Techniques; Electrospinning; Sublingual; SUS; techniky in vitro; sumatriptan; prasata; Administration, Sublingual; Mouth Mucosa; Nanofibers; NAPS; naproxen sodium; Anti-Inflammatory Agents, Non-Steroidal; ústní sliznice; Swine; Vasoconstrictor Agents; Drug Delivery Systems; vazokonstriktory; lékové transportní systémy; zvířata; Sumatriptan; NAP; Nanofibre; Naproxen; naproxen